Correlation Analysis between Physical Literacy, Physical Activity, and Physical Fitness in Students of SMA 1 Kolaka - Haris, Iyan; Yulianto, Ari; Ernawati, Ernawati; Basrawi, Basrawi; Sari, Tri (Journal of Physical and Outdoor Education, 2024)
This study aims to analyze the correlation between physical literacy, physical activity, and physical fitness among students of SMA 1 Kolaka. Using a cross-sectional research design, this study involved 200 randomly selected students. Data were collected through physical literacy questionnaires, physical activity records, and physical fitness tests. Data analysis employed Pearson correlation tests and multiple linear regression. Results showed significant positive correlations between physical literacy and physical activity (r = 0.68, p < 0.001) and physical fitness (r = 0.72, p < 0.001). Physical activity also positively correlated with physical fitness (r = 0.75, p < 0.001). Regression analysis revealed that physical literacy and physical activity together explained 65% of the variation in students' physical fitness. These findings emphasize the importance of enhancing physical literacy and promoting physical activity to improve high school students' physical fitness.